Examining the Impact of Modern Social Media on Sports Tourism Marketing in Ardabil Province - Namvar Goli daragh, Samira; Mokhtari Yoznab, Robab; Skandari Dastgiri, Simin (Business, Marketing, and Finance Open, 2025)
Tourism is one of the key economic sectors that has been recognized as a clean industry, contributing significantly to national economic growth by increasing foreign exchange earnings, boosting employment, and generating income. This study is a mixed-methods research (quantitative and qualitative) and is categorized as a survey-based and grounded theory study in terms of methodology. The qualitative phase involved a sample of 15 experts, including university professors in sports management and tourism specialists, who were interviewed. The study followed three fundamental stages of coding. In the quantitative phase, the target population consisted of sports tourists in Ardabil Province, who responded to a 24-item questionnaire using a Likert scale. Given the indefinite size of the statistical population, it was considered unlimited, and based on Cochran’s formula for an unlimited population, the sample size was determined to be 384 participants. A total of 400 questionnaires were distributed, and ultimately, 380 valid questionnaires were collected using a simple random sampling method. Data analysis was conducted using SPSS and Lisrel software, employing structural equation modeling tests. The results of the research questions indicate that all five examined factors demonstrated that the consequences of introducing sports tourism marketing include (tourism marketing through media, the impact of sports tourism development in the region, tourist attraction and retention, tourism economy, and cultural tourism). The causal factors influencing sports tourism marketing (sports managers' and specialists' policies, cultural-sports tourism potentials, and regional transformations) play a crucial role in the development of sports tourism marketing in Ardabil Province, with an emphasis on modern social media.